2021
DOI: 10.3390/jcm10214880
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Mycobacterium chimaera and tuberculosis Using Ocular Multimodal Imaging: A Systematic Review

Abstract: Due to their non-specific diagnostic patterns of ocular infection, differential diagnosis between Mycobacterium (M.) chimaera and tuberculosis can be challenging. In both disorders, ocular manifestation can be the first sign of a systemic infection, and a delayed diagnosis might reduce the response to treatment leading to negative outcomes. Thus, it becomes imperative to distinguish chorioretinal lesions associated with M. chimaera, from lesions due to M. tuberculosis and other infectious disorders. To date, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…OCT technology is also widely used for posterior segment imaging; several studies have shown its effectiveness in disease monitoring with good intrasession reproducibility even in case of corneal pathologies (Reibaldi et al, 2012), as well as in detecting the onset of possible treatment-related complications (Ceravolo et al, 2020;Arumuganathan et al, 2021). Furthermore, it is commonly used as a screening tool for not only ocular diseases but also systemic diseases (Chisari et al, 2019;Carnevali et al, 2021;Koman-Wierdak et al, 2021;Wiest et al, 2021;Zweifel et al, 2021). Recently, AS-OCT has been introduced as a valid tool to optimize the classification of Stage 3 NK (Mastropasqua et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…OCT technology is also widely used for posterior segment imaging; several studies have shown its effectiveness in disease monitoring with good intrasession reproducibility even in case of corneal pathologies (Reibaldi et al, 2012), as well as in detecting the onset of possible treatment-related complications (Ceravolo et al, 2020;Arumuganathan et al, 2021). Furthermore, it is commonly used as a screening tool for not only ocular diseases but also systemic diseases (Chisari et al, 2019;Carnevali et al, 2021;Koman-Wierdak et al, 2021;Wiest et al, 2021;Zweifel et al, 2021). Recently, AS-OCT has been introduced as a valid tool to optimize the classification of Stage 3 NK (Mastropasqua et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous publications demonstrated that OCTA is able to detect alterations in the retinal microvasculature and could potentially be useful as an early diagnostic biomarker and for the follow-up examinations of patients affected by different systemic diseases [ 28 , 30 , 38 , 40 , 44 , 45 ]. In general, VD and VLD are OCTA biomarkers that have been used to assess the retinal microvasculature in different retinal and systemic diseases for years [ 24 , 28 , 29 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. While numerous findings on differences in VD and/or VLD in multiple diseases have been reported this study is the first to report on a statistically significant difference between an affected population (our FD cohort) and an HC group in VD/VLD ratio in DCP.…”
Section: Discussionmentioning
confidence: 99%
“…The fundus can show the specific state of the blood vessels in the retina of the patient, including the diameter of the blood vessels, the thickness of the wall, the degree of the curvature of the blood vessels, and the existence of new blood vessels. Fundus fluorescein angiography is an invasive diagnostic method for detecting fundus capillary circulation and vascular lesions, which can accurately guide subsequent laser treatment for the fundus lesions [ 58 , 59 ]. Optical tomography is a fast and noninvasive retinal imaging technology that has been widely employed in the detection of retinal layers.…”
Section: Introduction Of Optic Nerve Injury Ophthalmopathy and Animal...mentioning
confidence: 99%